Globalization and social integration: Patterns and processes - Cynthia Hewitt de Alcántara; Dharam Ghai (United Nations Research Institute for Social Development (UNRISD), 1994)
Social integration is a broad and ambiguous term, variously understood by different people. To some, it is a positive goal, implying the promotion of well-ordered and harmonious relations at all levels of society. To others, increasing integration has a negative connotation, conjuring up the image of an unwanted imposition of uniformity. For a third group, the term implies neither a positive nor a negative state. It is simply an invitation to analyse the established patterns of human relations and values which tie people to one another in any given time and place, defining the parameters of their life chances. In this paper, the latter approach will be adopted: patterns and processes of integration are phenomena to be studied, not goals to be attained. Accepting such a premise makes it easier to explore the underlying causes of growing violence, deepening inequality and lack of solidarity throughout much of the modern world.
Keywords: 330